Pengaruh Mekanisme Good Corporate Governance terhadap Nilai Perusahaan - Muhammad Fadli Alfarisy; Yuni Rosdiana (UNISBA Press, 2022)
Abstract. The implementation of Good Corporate Governance in Indonesia is still relatively low, although currently companies are competing to implement Good Corporate Governance, but it is only limited to meeting business requirements and demands; has not become a voluntary awareness as part of business ethics. This study aims to determine the effect of good corporate governance mechanisms on the value of manufacturing companies on the IDX in 2015-2019. The research method is verification with a quantitative approach. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange inY2015-2019 with a total sample of 10 companies. The data collection technique used is secondary data through the company's annual report. This data analysis technique uses multiple regression analysis. The results of the study show that the independent board of commissioners has an effect on the value of manufacturing companies on the IDX in 2015-2019; institutional ownership has no effect on the value of manufacturing companies on the IDX in 2015-2019; the audit committee has an effect on the value of manufacturing companies on the IDX in 2015-2019. Abstrak. Implementasi Good Corporate Governance di Indonesia masih tergolong rendah, walaupun saat ini perusahaan berlomba-lomba untuk melaksanakan Good Corporate Governance, namun baru sebatas pada pemenuhan ketentuan dan tuntutan bisnis; belum menjadi kesadaran secara sukarela sebagai bagian dari etika bisnis. Penelitian ini bertujuan untuk mengetahui pengaruh mekanisme good corporate governance terhadap nilai perusahaan manufaktur di BEI tahun 2015-2019. Metode penelitian adalah verifikatif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di BEI tahun 2015-2019 dengan jumlah sampel sebanyak 10 perusahaan. Adapun teknik pengumpulan data yang digunakan adalah data sekunder melalui laporan tahunan perusahaan. Teknik analisis data ini menggunakan analisis regresi berganda. Hasil penelitian menunjukan bahwa dewan komisaris independen berpengaruh terhadap nilai perusahaan manufaktur di BEI Tahun 2015-2019; kepemilikan institusional tidak berpengaruh terhadap nilai perusahaan manufaktur di BEI Tahun 2015-2019; komite audit berpengaruh terhadap nilai perusahaan manufaktur di BEI Tahun 2015-2019.